Tripartite organizational partnerships and the wickedness of the water and sanitation sector in Brazil: an institutional analysis - Carvalho, Denise Moraes (2019)
This study aims to investigate the institutional constraints on the water and sanitation sector in Brazil that can affect the governance of tripartite partnerships (TPPs) and compromise its viability. The analysis of the institutional constraints was expressed in terms of voids, complementarities and logics. State-level discussion shows that governments carry resilient elements of institutional constraints that make difficult to discuss agency, administrative structure and the relationship between the spheres of the government, as well as questions about the effectiveness of the existent rules and laws. By a progressive case study approach we analyzed two Dutch partnership case studies – in Ghana and in Kenya - and one Brazilian case study (SISAR/Ceará). The case studies were analyzed by the lens of configurations, through the combination of strengths of the typological and taxonomic approaches, using the Dutch partnerships as the basis for the analysis of the Brazilian case study, SISAR. The Brazilian water and sanitation problems were classified as ‘wicked’ or collective action problems. Wicked problems resulted of numerous voids in the sector, as the regulatory and enforcement voids and we discussed the idea of partnering as a counter-argument for institutional voids. The TPPs emerged as a potential solution for dealing with wicked problems as they present institutional characteristics from different spheres (public and private, profit and non-profit and governmental and non-governmental) and a bundle of different logics to the provision of services and goods. When organizations are exposed to different logics, they suffer from tensions that can become real challenges to be faced. The different formats of conceptions in partnerships were translated into configurations types and each type showed a different way of relating to the 'wickedness' of problems. By the configuration structure it was possible to analyze the dynamic between the different types of TPPs. The different reactions to wicked problems in the empirical world are presented in this study in the form of institutional constraints that can restrict or enable the emergence of the TPPs and influence their governance arrangements. The TPPs configurations can be pulled according to the dominant logic that expose the different balances of forces between sectors. These forces were unfolded in dimensions that characterized each type of configuration. The wickedness of the water and sanitation’s problems were possible to be empirically identified, with the help of configurations. We conducted a qualitative research and we used data from semi structured interviews with people involved on the basic sanitation sector in the Netherlands, Ghana, Kenya and Brazil, as well as documentary sources. The lessons learned, pointed that institutional capacity is important for experiences in partnerships as well as the empowerment of civil society for a more effective participation. When the Dutch examples were transposed to the Brazilian case, elements inherent to the local context and related to institutional constraints emerged, which deserved to be discussed in a deeper way, being necessary to articulate these elements between the state level and that of the arrangements in partnerships, in order to analyze how they can interfere in their governance structures. The institutional complementarities observed in this study have demonstrated that there are incompatibilities in the water and sanitation sectors regarding to the plurality of the regulatory system, the existence of duplicity in the actors’ roles, as well as contradictions in the rules. A relevant aspect of institutional voids concerns the lack of a sector’s macro-level alignment, at a federal level, to set a standard of reference norms and guidelines for all regulatory agencies operating in the country. The state-centered mode with strong emphasis on the relation between public and private sector, and the little appreciation of civil society were the main institutional constraints identified in terms of logics.